Characterization of Md5-BAC-REV-LTR virus as Marek’s disease vaccine in commercial meat-type chickens: protection and immunosuppression - C., Ellington; A. L., Cortes; Nik Mohd Azmi, Nik Mohd Faiz; J. K., Mays; Fadly, Aly; Silva, Robert F.; I. M., Gimeno (Taylor and Francis, 2021)
Md5-BAC-REV-LTR is a recombinant Marek’s disease virus (MDV), with an insertion of the long terminal repeat (LTR) of reticuloendotheliosis virus (REV) into the genome of the highly virulent MDV strain rMd5. It has been shown that Md5-BAC-REV-LTR does not induce tumours and confers high protection against challenge with MDV in 15 × 7 chickens. The objective of the present study was to evaluate the protection and safety (in terms of oncogenicity and immunosuppression) of Md5-BAC-REV-LTR in commercial meat-type chickens bearing maternal antibodies against MDV. Our results show that sub-cutaneous administration of Md5-BAC-REV-LTR at 1 day of age conferred high protection (protection index PI = 84.2) against an early challenge (1 day) by contact exposure to shedder birds infected with the vv+ MDV 648A strain. In such stringent challenge conditions, Md5-BAC-REV-LTR was more protective than a commercial CVI988 (PI = 12.4) and similar to the experimental vaccine Md5-BACΔmeq (PI = 92.4). Furthermore, Md5-BAC-REV-LTR did not induce either tumours or immunosuppression in this study. Immunosuppression was evaluated by the relative lymphoid organ weights and also by the ability of the vaccine to induce late-MDV-induced immunosuppression associated with reactivation of the virus. This study shows that Md5-BAC-REV-LTR has the potential to be used as a MD vaccine and is highly protective against early challenge with vv+ MDV.